obtain the general and particular solution for differential equation below
(y - √x2+y2) dx - xdy = 0 when x=√3, y=1
Rearranging gives:dy
"\\frac{dy}{dx}= \\frac{y+ \\sqrt{x^2+y^2}}{x}= \\frac{y}{x}+ \\sqrt{1+ (\\frac{y}{x})^2}"
Try substituting u=y/x.
Then y′=u+xu′, giving:
"xu'= \\sqrt{1+u^2}"
"\\frac{u'}{ \\sqrt{1+u^2}}= \\frac{1}{x}"
sinh-1u=c+ log(x)
u=sinh(c+ log(x))
General solution
"y=x sinh(c+ log(x))=x \\frac{e^{c+log(x)}. - e^{-c-log(x)}}{2}=x \\frac{e^ce^{log(x)}- 1\/e^ce^{log(x)}}{2}"
"2= \\sqrt{3}( \\sqrt{3}e^c -1\/ \\sqrt{3}e^c) =3e^c -1\/e^c"
"3e^{2c}-2e^c-1=0"
D=4+12=16
"e^c= \\frac{2^+_- \\sqrt{16}}{6}"
ec1=1
ec2= -1/3
Particular solution
"y_1=x \\frac{e^{log(x)}-1\/e^{log(x)}}{2}"
"y_2=x \\frac{-1\/3e^{log(x)}+ 3\/e^{log(x)}}{2}"
Comments
Leave a comment